Malim : jurnal pengajian umum Asia Tenggara = \b Southeast Asia journal of general studies - \a Universiti Kebangsaan Malaysia. \b Pusat Pengajian Umum (\a [Bangi, Selangor] : \b Pusat Pengajian Umum, Universiti Kebangsaan Malaysia, \c 2000-, 2000)
\a Research studies on civilization, education, ethics, etc. in Malaysia
\a UKM: no.7 (Dis. 2006)-
\a Kepunyaan Koleksi Arkib (PTSL) : bil.1 (2000), bil.2 (2001), bil.3 (2002), bil.4, bil.5 (2004), bil.6 (2005), bil.7 (2006), bil.8 (2007), v.9 (2008)
\a In 2008, Jurnal Pengajian Umum changed their name to Malim : Jurnal Pengajian Umum Asia Tenggara (Southeast Asia Journal of General Studies)
]a Chiefly in Malay, some English; with summaries in English and Malay
Koleksi sumbangan : Prof. Dr. Supyan Husin.
Keywords: \a Scholarly periodicals \z Malaysia; \a Learned institutions and societies \z Malaysia \v Periodicals; \a Research \z Malaysia \v Periodicals